Role of hybrid tRNA-binding states in ribosomal translocation - Walker, Sarah E. (National Academy of Sciences, 2008)
During translation, tRNAs must move rapidly to their adjacent sites in the ribosome while maintaining precise pairing with mRNA. This movement (translocation) occurs in a stepwise manner with hybrid-state intermediates, but it is unclear how these hybrid states relate to kinetically defined events of translocation. Here we analyze mutations at position 2394 of 23S rRNA in a pre-steady-state kinetic analysis of translocation. These mutations target the 50S E site and are predicted to inhibit P/E state formation. Each mutation decreases growth rate, the maximal rate of translocation (k(trans)), and the apparent affinity of EF-G for the pretranslocation complex (i.e., increases K(1/2)). The magnitude of these defects follows the trend A > G > U. Because the C2394A mutation did not decrease the rate of single-turnover GTP hydrolysis, the >20-fold increase in K(1/2) conferred by C2394A can be attributed to neither the initial binding of EF-G nor the subsequent GTP hydrolysis step. We propose that C2394A inhibits a later step, P/E state formation, to confer its effects on translocation. Replacement of the peptidyl group with an aminoacyl group, which is predicted to inhibit A/P state formation, decreases k(trans) without increasing K(1/2). These data suggest that movements of tRNA into the P/E and A/P sites are separable events. This mutational study allows tRNA movements with respect to both subunits to be integrated into a kinetic model for translocation.